Optics-Butterfly-Phenomenon --- Double-slit, No-parallel-double-slit, Curve-double-slit, No-parallel-curve-double-slit - Peng, Hui (European Journal of Applied Sciences, 2026)
In this article, to study the mystery, we extend: the single-slit to curve-single-slit, and double-slit to non-parallel-double-slit to curve-double-slit to non-parallel-curve-double-slit experiments. We show the phenomena that the slight differences in the structures/shapes of slits produce profound different patterns, referred to it as “Optics-Butterfly-phenomenon”. The “Optics-Butterfly-Phenomenon” is helpful for thoroughly understanding the interference/diffraction phenomena of the optics. It is challenge to interpret “Optics-Butterfly-Phenomenon”.